2020
DOI: 10.1093/poq/nfaa015
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and the Changing Information Environment

Abstract: There is reason to believe that an increasing proportion of the news consumers receive is not from news producers directly but is recirculated through social network sites and email by ordinary citizens. This may produce some fundamental changes in the information environment, but the data to examine this possibility have thus far been relatively limited. In the current paper, we examine the changing information environment by leveraging a body of data on the frequency of (a) views, and recirculations through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…For example, it has been shown that an increasing proportion of the news consumers receive is not directly from news producers but is recirculated through social network sites. This, on the other side, may produce some important changes in the information environment (for example in the content of the most frequently shared news: Kraft et al 2020) and through that affecting the (ideological) strategy employed by newspapers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that an increasing proportion of the news consumers receive is not directly from news producers but is recirculated through social network sites. This, on the other side, may produce some important changes in the information environment (for example in the content of the most frequently shared news: Kraft et al 2020) and through that affecting the (ideological) strategy employed by newspapers.…”
Section: Discussionmentioning
confidence: 99%
“…We controlled for three content variables: news sentiment, COVID-19 news, and the number of tweets. It has been found that people are less inspired to share news containing negative sentiment (Kraft et al, 2020) or pandemic news (Sharma et al, 2017). For news sentiment, we employed Lexicoder Sentiment Dictionary developed by Young and Soroka (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies focused predominantly on the psychological mechanisms of corrections or the intention of information sharing (e.g., Mena, 2019), little is known about the effect of counteracting measures on actual behaviors (Margolin et al, 2018). However, information sharing is a social process in which people interact with others and participate in politics, and it is a key component of online expression and self-presentation (Kraft et al, 2020). In fact, sharing is central to the problem of information warfare (Woolley and Howard, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not just about being positive regarding favorable issues and negative toward unfavorable ones, but also using positively or negatively valenced emotionalism in messaging to affect engagement and efficacy. Thus, understanding the emotions that are embedded in political messaging is an important element in understanding how those messages affect the political attitudes and actions of consumers across multiple platforms (Kraft et al 2020). It also gives us additional clues into how parties and politicians see the value of particular issues, and how that issue may be used to win elections.…”
Section: Saying It With Some Feeling…mentioning
confidence: 99%